Global politics a new introduction - Edkins, Jenny; Zehfuss, Maja (Routledge is an imprint of the Taylor & Francis Group, an informa business, 2019)
This textbook provides a new way of teaching and learning about world politics. It engages directly with the issues in global politics that students are most interested in, helping them to understand the key questions and theories and also to develop a critical and inquiring perspective